Assessing the Effectiveness of National Wetland Adaptation and Management Frameworks in Kenya; The case of Nyando Wetland Ecosystem - Ongoro, Wilver (Université d'Ottawa | University of Ottawa, 2017)
Wetlands are among the world’s most productive ecosystems. They are considered vital for sustainable development and human well-being. Development and implementation of programs for sustainable management and conservation of these wetlands, as well as for climate change adaptation, in resource poor settings of low and middle income countries remains a major challenge. In the face of climate change that is largely driven by richer countries due to their larger carbon footprint, the burden of disrupted livelihoods as a result of climate change, will disproportionately fall on poor communities like those residing along the Nyando wetland basin in western Kenya. This paper describes the Nyando Wetland ecosystem and its challenges and uses it as a case study to demonstrate the complexities of developing sustainable wetland management and climate change adaptation programs in a low and middle income country. The current Kenya national framework (environment), policy documents and strategies have been outlined and measured against international best principles and practices for wetland management and climate change adaptation. This framework has also evaluated for feasibility. In general, the framework is extensive and suitable and identifies all the main stakeholders and provides an excellent grasp of the challenges. Legislative documents are responsive to the problems identified. Nonetheless, there remain a few challenges, including lack of coherent institutional frameworks to provide coordinated programs, lack of sufficient mechanisms to involve local populations, lack of capacity to analyze and interpret data and absence of capacity for long term ecosystem service monitoring and economic analysis. More importantly, the socio-political and legal context of this framework is complicated by poor governance systems where political will to maintain responsible and accountable use of public resources is lacking. In addition, there is strong intention to prepare communities around wetlands for climate change, but adaptation mechanisms are not well described and pathways to obtain the best information for decision making are not well described. The formation of lean organizations with sufficient local participation and with the required capacity will be instrumental in developing and implementing relevant and context-specific wetland management and climate change adaptation programs in Nyando and other wetlands and ecosystems in Kenya. Notably, sustainable wetland management and climate change adaptability can only successfully be implemented if accompanied by socio-political reforms that achieve better governance and accountability.